Inhibitory Factors of Reflective Teaching Practices: English Teachers' Perspectives - Fransiskus Jemadi; Fatmawati Fatmawati; Leonardus Par; Yulian Juita Ekalia; Adrianus Nabung (Universitas Hamzanwadi, 2023)
The role of reflection in enhancing teacher professional development and its impact on the quality of education is widely recognized. By reflecting on their teaching practices, teachers can make more informed decisions when planning, implementing, and evaluating their teaching activities. This study aims to identify the inhibitory factors that prevent EFL teachers from engaging in reflective teaching practices. The study utilized the Inhibitors to EFL Teachers' Reflective Teaching Questionnaire (IETRTQ) to gather data from 97 English teachers in junior high schools in East Manggarai regency, East Nusa Tenggara province, Indonesia. The data were analyzed using SPSS software to assess the level of agreement among participants regarding the inhibiting elements of reflective teaching practices in their teaching activities. The findings suggest that the teachers had a moderate awareness of the inhibitory factors that hinder their reflective teaching practices, with 69 teachers (71.13%) acknowledging these barriers. The implications of these findings are discussed, highlighting the need for targeted interventions and support to help teachers overcome these inhibitory factors and enhance their professional development.Bagian Atas Formulir